2007
DOI: 10.2459/01.jcm.0000281698.53983.4e
|View full text |Cite
|
Sign up to set email alerts
|

The cardiopulmonary exercise test is safe and reliable in elderly patients with chronic heart failure

Abstract: In elderly patients with CHF, the CPX is safe, feasible and able to provide basic information for individual risk assessment. These findings potentially extend the indications of CPX, which is currently applied to selected middle-aged patients with CHF, to the elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 18 publications
3
25
0
4
Order By: Relevance
“…Scardovi et al showed that CPET was safe and feasible in HF patients aged ≥70 years, reporting also a high proportion of subjects who reached a significant respiratory exchange ratio and a detectable AT. 29 In the present study AT was detectable in 74% of patients aged ≥70 years, with a reduction of V O2 at AT in comparison with other subgroups, showing that submaximum exercise parameters are reduced in older patients and may be a marker of worse prognosis, as confirmed by a recent study. 30 In a subanalysis of the Heart Failure: A Controlled Trial Investigating Outcomes of Exercise TraiNing (HF-ACTION), the authors observed a decrease in peak V O2 and a concomitant increase in V E/V CO2 in patients aged ≥70 years, compared with younger patients.…”
Section: Discussionsupporting
confidence: 69%
“…Scardovi et al showed that CPET was safe and feasible in HF patients aged ≥70 years, reporting also a high proportion of subjects who reached a significant respiratory exchange ratio and a detectable AT. 29 In the present study AT was detectable in 74% of patients aged ≥70 years, with a reduction of V O2 at AT in comparison with other subgroups, showing that submaximum exercise parameters are reduced in older patients and may be a marker of worse prognosis, as confirmed by a recent study. 30 In a subanalysis of the Heart Failure: A Controlled Trial Investigating Outcomes of Exercise TraiNing (HF-ACTION), the authors observed a decrease in peak V O2 and a concomitant increase in V E/V CO2 in patients aged ≥70 years, compared with younger patients.…”
Section: Discussionsupporting
confidence: 69%
“…Scardovi et al examined 227 elderly patients with CHF who underwent 395 cardiopulmonary exercise tests. 26 No adverse events were observed. Sun et al also noted no adverse events in 53 patients with primary pulmonary hypertension who underwent CPX.…”
Section: Discussionmentioning
confidence: 98%
“…As such, there is limited published data addressing the safety of CPX in these patient subsets. [25][26][27] The purpose of this study was to examine the safety of CPX in a large, heterogeneous cohort of high-risk patients with a wide variety of underlying high-risk cardiovascular diagnoses.…”
Section: Clinical Perspective On P 2472mentioning
confidence: 99%
“…A summary of 19 different reports (1971-2012) involving >2.1 million exercise tests is given in Table 3, with specific reference to year of publication, morbidity and mortality rates, total complications, and direct supervision (ie, physician versus nonphysician). [5][6][7][8][9]11,[28][29][30][31][32][33][34][35][36][37][38][39][40] Subjects included apparently healthy individuals and adults with known or suspected cardiovascular disease, athletes, and patients with a history of high-risk cardiac conditions, including chronic heart failure (ie, New York Heart Association class II-IV heart failure caused by left ventricular systolic dysfunction), hypertrophic cardiomyopathy, pulmonary hypertension, aortic stenosis, malignant ventricular arrhythmias, or combinations thereof. Complications were defined primarily as the occurrence of acute myocardial infarction or exercise-induced threatening arrhythmias (ventricular tachycardia, ventricular fibrillation, or marked bradycardia) that mandated immediate medical treatment.…”
Section: Risk Of Exercise Testing By Physician and Nonphysician Healtmentioning
confidence: 99%